LOCAL FLAPS USED IN FACIAL RECONSTRUCTION AFTER THE EXCISION OF CUTANEOUS CARCINOMAS -RETROSPECTIVE STUDY - Alexandra Crăcană; Victor-Vlad Costan; Andrei Nicolau; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2016)
The incidence of skin carcinomas on the face varies significantly by geographical area, in Romania being 10 in 100.000 inhabitants. Aim of the study: To determine the incidence, clinical characteristics and histopathological types of facial cutaneous carcinomas, as well as the types of local flaps used in the reconstruction of facial cutaneous defects consecutive to the excision of carcinomatous lesions. Material and methods: The study was conducted on a representative sample made of 342 patients on two main directions: clinical and computer-assisted statistical. Results: Basal cell carcinoma was diagnosticated in 69% cases of whom 51.7% were male, mostly aged over 60. Rotation flap was the first option for most patients requiring local flaps plasty of postoperative defect (51%). Conclusions: The interventions using local flaps provide the possibility of restoring aesthetic function; their colour and texture are similar to the skin of the postoperative defect region.